School staffs' views on student non-attendance: a systematic literature review - George Alaimo; Catherine Kelly (Frontiers in Education)
IntroductionThe views of school staff on student non-attendance have scarce representation in the existing literature. This systematic literature review explores the perspectives of school staff on student non-attendance, synthesizing findings from eleven qualitative and mixed-method papers.MethodsUsing a thematic synthesis approach, the review investigates how non-attendance is conceptualized by school staff and the extent to which their perspectives reflect its multidimensional nature.ResultsSchool staff described the factors contributing to student non-attendance as: (1) within-child, such as anxiety, mental health, and special educational needs; (2) home environmental influences, including parenting styles and attachment needs; (3) school-related factors such as academic pressures, unsuitable curricula, and peer rejection; and (4) the emotional and resource strain experienced by school staff.DiscussionFindings suggest that conceptualizations of non-attendance, such as “emotionally based school avoidance” (EBSA) or “school refusal,” may influence staff interpretations and strategies for intervention. Eco-systemic approaches emphasizing collaborative relationships between schools, families, and external agencies are highlighted by school staff. This review underscores the need for flexible, context-sensitive approaches to support attendance, informed by clear, strengths-based terminology and increased collaboration between stakeholders. Future research should explore the integration of systemic models into school policies and address the well-being of staff supporting student non-attendance.